A global game analysis of the LLR: the role of creditors' behaviour and penalty rate lending. (2015) - Shino, Junnosuke
We construct a global-game LLR model in which the policy maker to provide LLR is an explicit player that cannot distinguish solvent from insolvent banks ex ante. We first show that creditors' aggregate behaviour to withdraw their funds operates as a signal to the policy maker about banks' solvency. Then it is shown that the policy maker optimally helps only illiquid but solvent banks and the lending rates are strictly positive whenever LLR is utilised. The rates can be seen as 'conditionally punitive' in the sense that they take the highest level under the restriction that the solvent borrowers survive.